Design of a Portable Tidal Power Plant (PLTPS) Using Static Feet - Abror, Rahmatul; Wicaksono, Indro; Izzuddin, Ahmad (ENERGY: JURNAL ILMIAH ILMU-ILMU TEKNIK, 2022)
The potential of marine energy to generate electricity is one of the potentials that is not widely known to the  general  public.  One  of the  natural  phenomena that  can be  used  as  a  power  plant  is the tides  of  sea  water. Tidal Power Plant is a power plant using sea water when it is high tide and using estuary water power when the sea  water  is  receding.  Tidal  Power  Plants  are  generally  built  permanently  using  dams,  then  a  Portable  Tidal Power Plant is developed that can be placed on the beach when the tide is high and in the estuary when the sea water  is  receding. The  method  used  in  this  research  is  the  experiment  method  on  Portable  Tidal  Power  Plant. The Portable Tidal Power Plant uses seawater and estuary water to turn the mill, then the windmill will produce mechanical energy, and the generator will convert the mechanical energy from the wheel into electrical energy. The Portable Tidal Power Plant was tested on the beach when the sea water is high, the highest voltage is 3.3 V and the highest RPM is 413 RPM. When tested on the estuary when the sea water is receding, the highest voltage is 2.6 V and the highest RPM is 284.4 RPM